The Role of Product Quality and Consumer Satisfaction in Increasing Consumer Loyalty (Marketing Management Literature Review) - Aprelyani, Siska (Greenation International Journal of Engineering Science, 2023)
Literature Review The Role of Product Qualityand Consumer Satisfaction in Increasing Consumer Loyalty is a scientific article with the aim of analyzing whether product quality and consumer satisfaction play a role in consumer loyalty. The method of writing a literature review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other online media. The results of this article are: 1) Product Quality plays a role in Consumer Loyalty; 2) Consumer Satisfaction plays a role in Consumer Loyalty; Apart from these 3 exogenous variables that influence the endogenous variable of Purchasing Decisions, there are still many other factors including brand image, promotion, price.